2018
DOI: 10.1159/000491719
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivation of the Frontal Control Network Revealed by Symptom Provocation in Obsessive-Compulsive Disorder Using EEG Microstate and sLORETA Analyses

Abstract: The aim of this study was to investigate the changes of brain electric field induced by symptom provocation in patients with obsessive-compulsive disorder (OCD) in comparison to healthy controls in the resting state. For this purpose, EEG recordings in conditions of initial rest, clean control, symptom provocation by imaginal exposure, and final rest were used for computing spatiotemporal activity characteristics based on microstate segmentation. Within-group comparisons were significant for the symptom provoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
3
7
0
Order By: Relevance
“…In our study, frequent switches between different functional states of OCD also support characteristics of more changes in the dynamic functional network in OCD and manifest this change as a numerical indicator. In addition, the electroencephalogram study on OCD also showed that compared with HC, functional states in OCD groups were obviously unstable, and the conversion rate between states was significantly increased, 51 which is similar to what we have found in this study. In the study of dFNC in schizophrenia, there was a significant reduction in the number of transitions between states, and it was speculated that the temporal dynamics of the brain network in schizophrenia were seriously and universally changed 24 .…”
Section: Discussionsupporting
confidence: 89%
“…In our study, frequent switches between different functional states of OCD also support characteristics of more changes in the dynamic functional network in OCD and manifest this change as a numerical indicator. In addition, the electroencephalogram study on OCD also showed that compared with HC, functional states in OCD groups were obviously unstable, and the conversion rate between states was significantly increased, 51 which is similar to what we have found in this study. In the study of dFNC in schizophrenia, there was a significant reduction in the number of transitions between states, and it was speculated that the temporal dynamics of the brain network in schizophrenia were seriously and universally changed 24 .…”
Section: Discussionsupporting
confidence: 89%
“…Significant relationships between FC and clinical measures emerged. Specifically, executive networks FC has been predominantly positively associated with total severity scores, in line with evidence about hyper-responsiveness of cognitive control and monitoring systems at the basis of OCD manifestations (Bucci et al, 2004;Bucci et al, 2007;Endrass et al, 2010;Maltby et al, 2005;Riesel et al, 2014;Yoshimura et al, 2019). Nonetheless, relationships in the opposite direction (Xie et al, 2017) might challenge this assumption.…”
Section: Relationship Between Connectivity Patterns and Clinical Scoressupporting
confidence: 54%
“…The increased intra-network FC suggests an intrinsic aberrant recruitment of cognitive control processes. Indeed, OCD is thought to be characterized by over-recruitment of cognitive control (Bucci et al, 2004;Yoshimura et al, 2019). Specifically, hyperactivity and defective downregulation of monitoring processes were extensively reported (Bucci et al, 2007;Endrass et al, 2010;Riesel et al, 2014).…”
Section: Altered Connectivity Of Executive Networkmentioning
confidence: 99%
“…Relative to HC, we found that the GEV of patients with MA use disorder exhibited higher in microstate C, but lower for microstate B. Notably, patients with obsessive-compulsive disorder also have abnormalities in these two microstate classes [61]; that is, the occurrence of these microstates was significantly different from those of HC. Previous studies have also suggested similarities in the manifestation of visual and salience network networks in patients with obsessive-compulsive disorder and addiction [62][63][64][65][66][67].…”
Section: Microstatementioning
confidence: 62%